2020
DOI: 10.1002/jwmg.21832
|View full text |Cite
|
Sign up to set email alerts
|

Variation in True Metabolizable Energy Among Aquatic Vegetation and Ducks

Abstract: Avian diet quality is typically measured using true metabolizable energy (TME N ), which is a measure of assimilable energy of food items accounting for innate endogenous losses. Originally developed for use in the poultry industry, TME N methods have been adapted to determine the value of natural foods consumed by waterfowl to parameterize bioenergetics models for conservation planning. Because there is little knowledge of the variation in TME N estimates among food items and waterfowl species, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Our fifth and sixth wetland categories were derived from a regional waterfowl‐focused land cover layer of unharvested flooded agriculture and intensively managed emergent wetlands, which were hand‐digitized and combined with our CDL base layer (Highway, 2022; Masto, 2023; Palumbo et al, 2019). Final wetland classifications included six wetland types that were presumed to generally increase in energetic quality based on extensive published literature (i.e., open water < woody wetlands < emergent wetlands < managed emergent wetlands < harvested agriculture < unharvested agriculture; Foster et al, 2010; Gross et al, 2020; Hagy et al, 2011; Hagy & Kaminski, 2012; Kaminski et al, 2003; Osborn et al, 2017; Tapp et al, 2018; Table 1; Appendix S1). However, we did not assign energy values to our categorical wetland variables explicitly; instead, we assumed their energetic quality, in a similar fashion to North American conservation planning initiatives and their partners (Edwards et al, 2012; Hagy et al, 2021; Hagy, Wirwa, Hitchcock, 2021; Soulliere et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Our fifth and sixth wetland categories were derived from a regional waterfowl‐focused land cover layer of unharvested flooded agriculture and intensively managed emergent wetlands, which were hand‐digitized and combined with our CDL base layer (Highway, 2022; Masto, 2023; Palumbo et al, 2019). Final wetland classifications included six wetland types that were presumed to generally increase in energetic quality based on extensive published literature (i.e., open water < woody wetlands < emergent wetlands < managed emergent wetlands < harvested agriculture < unharvested agriculture; Foster et al, 2010; Gross et al, 2020; Hagy et al, 2011; Hagy & Kaminski, 2012; Kaminski et al, 2003; Osborn et al, 2017; Tapp et al, 2018; Table 1; Appendix S1). However, we did not assign energy values to our categorical wetland variables explicitly; instead, we assumed their energetic quality, in a similar fashion to North American conservation planning initiatives and their partners (Edwards et al, 2012; Hagy et al, 2021; Hagy, Wirwa, Hitchcock, 2021; Soulliere et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…As proof, Lancaster et al, (2018) showed that bioavailable energy particularly total metabolizable energy (TME) of submersed aquatic vegetation, was highly variable among duck species, favoring mallard ducks compared with gadwall (Mareca Strepera). A recent study demonstrated a similar result that mallards had slightly greater nitrogen-corrected total metabolizable energy (TME N ) than gadwall (Mareca Strepera) for submersed aquatic vegetation species such as Canadian waterweed (Elodea canadensis; 1.66 ± 0.26), followed by coontail (Ceratophyllum demersum; 1.51 ± 0.28), southern naiad (Najas guadalupensis; 1.37 ± 0.39), sago pondweed (Stuckenia pectinata; 0.50 ± 0.22), wild celery (Vallisneria americana; 0.05 ± 0.42), and Eurasian watermilfoil (Myriophyllum spicatum; -0.13 ± 0.42) (Gross et al, 2020). Likewise, the degree of growth is also a factor that influences energy metabolism and consequent utilization.…”
Section: A Feed Energy Utilization With Emphasis On Ducksmentioning
confidence: 99%
“…In addressing the unexpected tendency of certain guilds to decrease despite more abundant SAV, many interviewees noted the importance of vegetative community composition and its relationship to waterfowl foraging behaviour. For instance, assimilable energy may provide insight into the vegetation valued by waterfowl species within each guild (Dugger et al, 2007;Fredrickson & Reid, 1988;Gross et al, 2020). Southern naiad (Najas guadalupensis), wild celery (Vallisneria americana), coontail (Ceratophyllum demersum), sago pondweed (Potamogeton pectinatus), and Eurasian watermilfoil (Myriophyllum spicatum) are all important waterfowl resources found in Back Bay with varying degrees of tolerance to turbidity and salinity (Carter et al, 1983;Carter & Rybicki, 1991;Chamberlain, 1948;Tiner & Rorer, 1993) and varying degrees of true metabolizable energy for waterfowl (Gross et al, 2020).…”
Section: Informant Speculation Of Observed Trendsmentioning
confidence: 99%
“…For instance, assimilable energy may provide insight into the vegetation valued by waterfowl species within each guild (Dugger et al, 2007;Fredrickson & Reid, 1988;Gross et al, 2020). Southern naiad (Najas guadalupensis), wild celery (Vallisneria americana), coontail (Ceratophyllum demersum), sago pondweed (Potamogeton pectinatus), and Eurasian watermilfoil (Myriophyllum spicatum) are all important waterfowl resources found in Back Bay with varying degrees of tolerance to turbidity and salinity (Carter et al, 1983;Carter & Rybicki, 1991;Chamberlain, 1948;Tiner & Rorer, 1993) and varying degrees of true metabolizable energy for waterfowl (Gross et al, 2020). Moreover, diving ducks such as bufflehead (B. albeola) and mergansers (hooded [L. cucullatus] and red-breasted [Mergus serrator]) may be more tolerant of higher salinity conditions due to their ability to dive for marine crustaceans and molluscs (Perry et al, 2007).…”
Section: Informant Speculation Of Observed Trendsmentioning
confidence: 99%
See 1 more Smart Citation